2017
DOI: 10.1038/s41598-017-15939-9
|View full text |Cite
|
Sign up to set email alerts
|

EGFR conjunct FSCN1 as a Novel Therapeutic Strategy in Triple-Negative Breast Cancer

Abstract: Emerging evidence indicates that Fascin-1 (FSCN1) may possess a causal role in the development of several types of cancers and serves as a novel biomarker of aggressiveness in certain carcinomas. However, the regulatory mechanism of FSCN1 in triple-negative breast cancer (TNBC) cell invasion and migration is still largely unknown. In our study, we observed that the FSCN1 expression rates were significantly higher in invasive ductal carcinoma, compared with both usual ductal hyperplasia and ductal carcinoma in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 41 publications
2
33
0
Order By: Relevance
“…Fumagalli C et al (8) previously found that patients with TNBC carrying a silencing mutation in the O6-methylguanine DNA methyltransferase gene are associated with an increase in the susceptibility for alkylating agents. Wang et al (10) found that epidermal growth factor induced the expression of Fascin-1 through the activation of MAPK, which lead to poorer relapse-free survival and overall survival for patients with TNBC. However, since TNBC is associated with poor prognosis, identification of novel molecular biomarkers and development of treatment strategies are urgently sorted for unravelling the possible mechanisms of TNBC progression or improving patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Fumagalli C et al (8) previously found that patients with TNBC carrying a silencing mutation in the O6-methylguanine DNA methyltransferase gene are associated with an increase in the susceptibility for alkylating agents. Wang et al (10) found that epidermal growth factor induced the expression of Fascin-1 through the activation of MAPK, which lead to poorer relapse-free survival and overall survival for patients with TNBC. However, since TNBC is associated with poor prognosis, identification of novel molecular biomarkers and development of treatment strategies are urgently sorted for unravelling the possible mechanisms of TNBC progression or improving patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…IHC staining of paraffin-embedded tissue sections used the Envision System (Dako, Glostrup, Denmark), as described previously [ 5 , 30 ]. Primary antibodies consisted of anti-METTL14 mouse monoclonal antibody (clone CL4252, diluted at 1 : 1000; Abcam, Cambridge, England), ready-to-use anti-ER rabbit monoclonal antibody (clone SP1, Dako), ready-to-use anti-PR mouse monoclonal antibody (clone PgR636, Dako), HercepTest (Dako), and ready-to-use anti-Ki-67 mouse monoclonal antibody (clone MIB-1, Dako).…”
Section: Methodsmentioning
confidence: 99%
“…IHC staining of paraffin-embedded tissue array sections was conducted using the Envision System (Dako, Glostrup, Denmark), as described previously 25 , 26 . Briefly, the sections were submerged in boiling sodium citrate (pH, 6.0) for 2 min in a pressure cooker.…”
Section: Methodsmentioning
confidence: 99%